A multifilamented electrode in the middle cardiac vein reduces energy requirements for defibrillation in the pig. Issue 4 (1st October 2000) - Roberts, P R; Allen, S; Betts, T; Urban, J F; Euler, D E; Crick, S; Anderson, R H; Kallok, M J; Morgan, J M
Abstract : OBJECTIVE: To compare the defibrillation efficacy of a novel lead system placed in the middle cardiac vein with a conventional non-thoracotomy lead system. METHODS: In eight pigs (weighing 35–71 kg), an electrode was advanced transvenously to the right ventricular apex (RV), with the proximal electrode in the superior caval vein (SCV). Middle cardiac vein (MCV) angiography was used to delineate the anatomy before a three electrode system (length 2 × 25 mm + 1 × 50 mm) was positioned in the vein. An active housing (AH) electrode was implanted in the left pectoral region. Ventricular fibrillation was induced and biphasic shocks were delivered by an external defibrillator. The defibrillation threshold was measured and the electrode configurations randomised to: RV→AH, RV+MCV→AH, MCV→AH, and RV→SCV+AH. RESULTS: For these configurations, mean (SD) defibrillation thresholds were 27.3 (9.6) J, 11.9 (2.9) J, 15.2 (4.3) J, and 21.8 (9.3) J, respectively. Both electrode configurations incorporating the MCV had defibrillation thresholds that were significantly less than those observed with the RV→AH (p < 0.001) and RV→SCV+AH (p < 0.05) configurations. Necropsy dissection showed that the MCV drained into the coronary sinus at a location close to its orifice (mean distance = 2.7 (2.2) mm). The MCV bifurcated into two main branches that drained the right and left ventricles, the left branch being the dominant vessel in the majority (6/7) of cases. CONCLUSIONS: Placement of specialised defibrillation electrodes within the middle cardiac vein provides more effective defibrillation than a conventional tight ventricular lead.